An adaptive E-learning Framework to supporting new ways of teaching and learning - Khalid, S.U.; Basharat, A.; Shahid, A.A.; Hassan, S. (2009 International Conference on Information and Communication Technologies, 2009)
To address the ever increasing need and challenges associated with improving the state of Web-based education, a synergistic view of e-learning and intelligent and adaptive tutoring is adapted which is the basic essence of the learner centered adaptive e-learning framework presented in this paper. This framework aims to provide a complete environment of online learning. The conceptual architecture of the framework presented in this paper is centered around the following core features: (1) domain specific learning services (2) student capability analysis (3) adaptive lecture authoring tool and notification manager (4) intelligent assessment engine (5) user friendly e-learning portal. Altogether, this framework is truly aimed to be an integrated platform consistent with the emerging needs of e-learning and distance education.